Barriers to pregnancy prevention for adolescents in rural Haiti: perceptions of healthcare providers - Shelbie Wooten; Emily Hurley; Nikolaus Schuetz; Melissa K. Miller; Jonathan Rodean; Emily Rupe; Kemi Lewis; Marie Daphnée Boncoeur; Abbey R. Masonbrink (BMC, 2024)
Abstract Background Little is known about healthcare providers' (HCPs) contraceptive views for adolescents in Haiti, who experience high rates of unintended pregnancy. We sought to describe HCPs' perspectives on barriers and facilitators to contraceptive care delivery in rural Haiti. Methods We conducted a cross-sectional survey and qualitative interviews with HCPs in two rural communities in Haiti from 08/2021-03/2022. We assessed demographics, clinical practice behaviors and explored contraception perspectives according to Theory of Planned Behavior constructs: attitudes, subjective norms, and perceived behavioral control (e.g., people's perceptions of their ability to perform a given behavior, barriers and facilitators of a behavior).15-17 We used descriptive statistics to report proportions and responses to Likert scale and multiple-choice questions. Guided by content analysis, we analyzed interview transcripts through thematic inductive coding and team debriefing. Results Among 58 respondents, 90% (n = 52) were female and 53% (n = 31) were nurses. Most reported always (n = 16, 28%) or very often (n = 21, 36%) obtaining a sexual history for adolescents. A majority agreed/strongly agreed that clinicians should discuss pregnancy prevention (n = 45, 78%), high-risk sexual behaviors (n = 40, 69%), and should prescribe contraception (n = 41, 71%) to adolescents. The most frequently cited provider-level barriers (i.e., significant or somewhat of a barrier) included insufficient contraception knowledge (n = 44, 77%) and time (n = 37, 64%). HCPs were concerned about barriers at the patient-level (e.g. adolescents' fear of parental notification [n = 37, 64%], adolescents will give inaccurate information about sexual behaviors [n = 25, 43%]) and system-level (e.g. resistance to providing care from administration [n = 33, 57%]). In interviews (n = 17), HCPs generally supported contraception care for adolescents. Many HCPs echoed our quantitative findings on concerns about privacy and confidentiality. HCPs reported concerns about lack of contraception education leading to misconceptions, and community and parental judgement. HCPs expressed interest in further contraception training and resources and noted the importance of providing youth-friendly contraceptive care. Conclusions While HCPs support contraceptive care, we identified actionable barriers to improve care for adolescents in rural Haiti. Future efforts should include increasing HCP knowledge and training, community and parent coalition building to increase contraception support and offering youth-friendly contraceptive care to offset risk for related adverse health outcomes in adolescents in rural Haiti.